Combination of trimetazidine and coenzyme Q10 for the treatment of acute viral myocarditis: a systematic review and meta-analysis - Zeng, Min; Chen, Zhi; Zhang, Yan; Pang, Yusheng (The Journal of Infection in Developing Countries, 2024)
Introduction: Coenzyme Q10 (CoQ10) is considered to be beneficial for patients with acute viral myocarditis (AVM). In addition, trimetazidine may be also beneficial to patients with AVM by promoting cardiac energy metabolism. This systematic review and meta-analysis examined the efficacy and safety of combining trimetazidine and CoQ10 with respect to CoQ10 alone in patients suffering from AVM. Methodology: PubMed, Embase, the Cochrane Library, Wanfang, and China National Knowledge Infrastructure (CNKI) databases were searched for relevant randomized controlled trials (RCTs). An analysis of random effects was employed to combine the results. Results: Sixteen RCTs that included 1,364 patients with AVM contributed to the meta-analysis. Overall, 687 patients received the combined treatment, while 677 received the CoQ10 alone for a duration of 2-12 weeks (mean: 5.2 weeks). In contrast to monotherapy with CoQ10, combined treatment with trimetazidine and CoQ10 significantly improved overall therapy effectiveness (risk ratio [RR]: 1.19, 95% confidence interval [CI]: 1.13 to 1.24, p < 0.001; I2 = 0%). Differences in study parameters such as the incidence of heart failure upon admission, dosage of CoQ10, or length of treatment did not significantly alter the outcomes (p for all subgroup analyses > 0.05). The combined treatment was associated with improved myocardial enzyme levels and recovery of cardiac systolic function as compared to CoQ10 alone (p all < 0.05). In addition, trimetazidine combined with CoQ10 caused no greater increase in adverse events than CoQ10 alone. Conclusions: Trimetazidine combined with CoQ10 is an effective and safe treatment for AVM.